Base of Skull Metastatic Adenocarcinoma from the Breast 23 Years after the Primary Diagnosis. (30th July 2020) - Othman, Iylia Ajmal; Zahedi, Farah Dayana; Husain, Salina
Abstract : Breast cancer metastases to the base of the skull with concomitant infiltration into the paranasal sinuses and nasopharynx are exceptionally rare with only small numbers of reported literatures. Greenberg et al. in 1981 described five clinical syndromes with regards to the base of skull metastases and the clinical presentation of each syndrome related to its anatomical location. Often, metastases to the base of the skull remain asymptomatic until the lesion has increased to a considerable size causing bony destruction and impingement to the surrounding structures. When involving the paranasal sinuses or nasopharynx, the most common presenting symptoms mimic those of rhinosinusitis and, hence, may delay the accurate diagnosis. We are reporting a case of base of skull metastasis from breast carcinoma, 23 years after the primary diagnosis. To the best of our knowledge, our case is the first case to report latent metastasis of more than 20 years.